Painless Biosensing for Non‐Invasive Health Monitoring: Advances, Platforms and Future Directions - Ayub Alam; Faiqa Gull; Muzammal Hameed; Iqra Iqbal; Saira Naz; Hadia Noor; Ammara Aslam; Sana Younis; Valentina Vit; Muhammad Aqib Mehmood; Nicola Coppedé (Electrochemical Science Advances, 2026)
ABSTRACT Non‐invasive biosensing has expanded blood‐based diagnostics into a growing set of accessible peripheral biofluids, yet most existing reviews remain confined to sweat, tears, saliva and urine, and treat the underlying literature descriptively rather than critically. Here, we present a review that extends this scope to include interstitial fluid and breath/exhaled breath condensate, two increasingly important non‐invasive matrices that have been largely absent from prior synthesis, and that explicitly distinguishes sensing strategies for small‐molecule metabolites from those for proteins and hormones, clarifying why the field has historically favoured the former and what emerging affinity‐based approaches (aptamers, molecularly imprinted polymers) are doing to close that gap. Beyond the electrochemical and optical platforms typically covered elsewhere, we introduce electrical, non‐faradaic transduction, including field‐effect transistor‐ and impedance‐based sensors, as a third major modality underpinning much of the current wearable sensor landscape. Rather than cataloguing individual devices, we critically compare reported sensitivity, selectivity and validation standards across studies within each biofluid class, highlighting where evidence is inconsistent or incomplete. Finally, we extend the discussion beyond device‐level advances to the translation barriers that determine real‐world deployment: the gap between laboratory demonstration and commercial product, regulatory pathways across major markets, patch‐to‐patch and device‐to‐device reproducibility and unresolved sensitivity/selectivity hurdles under real interferent conditions. Together, these additions position this review as a broader and more critically grounded synthesis of the painless biosensing landscape than currently available in the literature.